65.2k views
5 votes
What’s the answer
3(t – 1) = 2t + 9

2 Answers

6 votes
The answer would be t=12 the way you get there is by distributing the 3 to the t and -1. Now you have 3t-3=2t+9 then add the three in both sides making it 3t=2t+12 then subtract the 2t from both sides and you get your answer.
User Miligraf
by
5.0k points
1 vote

Answer:

T=12

Explanation:

User Icaruk
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.